Chemical Components of the Rhizome Oil of Curcuma Heyneana Val. - M. Sirat, Hasnah; Lee, Lay Meng (Malaysian Journal of Science, 2009)
The chemical composition of the essential oil of Curcuma heyneana isolated by hydrodistillation was analyzed by capillary GC and GC/MS. The main constituents found in the oil were sesquiterpenoids, curcumanolide (19.6%), dehydrocurdione (17.2%), isocurcumenol (16.5%), curcumenol (13.7%), curcumenone (6.4%), and germacrone (5.0%). A diterpenoid identified as labda-8(17), 12-diene-15, 16-dial (4.8%) was also found as one of the components in the oil. These constituents were also isolated and identified from the chloroform extract of the dried rhizomes.